Personal tax system: a comparison among Asean Commonwealth countries / Noor Hasimah M Yacob ... [et al.] - M Yacob, Noor Hasimah; Jamaluddin, Sabariah; Wan Abdul Rahman, Nor Hawani (Universiti Teknologi MARA Cawangan Pahang, 2019)
The primary purpose of taxation is to raise revenue for the country. A good, efficient and friendly tax system will raise more revenue to the government and will encourage a taxpayer to pay tax. Personal income tax is one of the taxes charged in every country for an individual taxpayer. The objectives of this study are to analyse and compare the difference between the personal tax system applied in Malaysia and other countries. The sample countries are chosen based on the list of Asean Commonwealth countries, namely Singapore, India, Sri Lanka, Bangladesh and Pakistan. The scopes of comparison are the scope of charge, determination of residence status, basis of assessment, types of income chargeable, tax rate, tax deductions, reliefs and rebates. The data is collected from the website of Inland Revenue of each sample countries based on 2017 and 2018’s rules and regulation. This study found that there is a difference between personal tax system applies in Malaysia and other study countries. However, Malaysia and Singapore have a quite a similar personal tax system regarding scope charge, types of income chargeable and reliefs available to a taxpayer. The findings of this study provide an input to the government and tax authorities in formulating tax policies. It also can be used by the public to get an idea regarding a personal taxation system among the sample countries and can help them to choose a tax haven country. This study is limited to the tax system applied for an individual having non-business income. It does not cover the taxability of business income and deduction for business expenses. This study can be extended to explore the taxability of business income and tax deduction for individual having business income.